2007
DOI: 10.1111/j.1469-8749.2007.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuromotor task training for children with developmental coordination disorder: a controlled trial

Abstract: The aim of this study was to evaluate neuromotor task training (NTT), a recently developed child-centred and taskoriented treatment programme for children with developmental coordination disorder (DCD). A treatment and a non-treatment control group of children with DCD were included. Children were selected if they scored below the 15th centile on the Movement Assessment Battery for Children (MABC). The children in the treatment group were recently referred for physiotherapy (n=26; 20 males, 6 females; mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
0
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 15 publications
(35 reference statements)
2
88
0
11
Order By: Relevance
“…Three of the studies reported their NTT effect sizes. Figure 5 displays the summation of these studies' findings.Researchers in one study were blinded to group allocation when assessing results (Niemeijer et al, 2007). In this study, the difference between the MABC pre-and postintervention scores were statistically significant in the intervention group (p = .003), while there was no significant change in scores in the control group.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Three of the studies reported their NTT effect sizes. Figure 5 displays the summation of these studies' findings.Researchers in one study were blinded to group allocation when assessing results (Niemeijer et al, 2007). In this study, the difference between the MABC pre-and postintervention scores were statistically significant in the intervention group (p = .003), while there was no significant change in scores in the control group.…”
mentioning
confidence: 78%
“…Physical therapists from the Netherlands developed a type of task-oriented training called neuromotor task training (NTT). NTT is based on a cognitive neuroscience approach to motor control (Niemeijer, Smits-Engelsman, & Schoemaker, 2007;, and uses a combination of motor learning and ecological principle of skill development through repeated learning sessions, as well as task and environmental constraint manipulations . A recent systematic literature review on the efficacy of motor interventions for children with DCD (task-oriented training, traditional physical and occupational therapy, process-oriented therapies, and chemical supplements) found evidence supporting traditional physical and occupational therapy and task-oriented interventions .…”
mentioning
confidence: 99%
“…Recently, interventions for motor coordination problems were reviewed (Wilson 2005). It seems that especially the child-centred and task-oriented methods that include cognitive components are useful therapies (Schoemaker et al 2003;Polatajko and Cantin 2005;Niemeijer et al 2007;Sugden 2007). Clinicians diagnosing and treating children and adolescents with ADHD should additionally assess whether motor coordination problems are present, and offer those with ADHD and co-existing motor coordination problems evidence-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Specific cognitive approaches that may be useful for children with differences in sensory processing and integration include problem-solving interventions such as the Cognitive Orientation to daily Occupational Performance (CO-OP; Polatajko & Mandich, 2004) and neuromotor task training (NTT; Niemeijer, Smits-Engelsman, & Schoemaker, 2007). Several studies support the use of CO-OP and NTT for children who have difficulties with motor coordination, including children with developmental coordination disorder (DCD) and ASD (Hyland & Polatajko, 2012;Rodger & Brandenburg, 2009;Rodger, Pham, & Mitchell, 2009;Smits-Engelsman et al, 2013).…”
Section: Child-focused Interventionsmentioning
confidence: 99%